1,Giải Pt a,(x-1) ²+(x+3) ²=2(x-2)(x+1)+38 b,5(x ²-2x-1)+2(3x-2)=5(x+1) ²

Question

1,Giải Pt
a,(x-1) ²+(x+3) ²=2(x-2)(x+1)+38
b,5(x ²-2x-1)+2(3x-2)=5(x+1) ²

in progress 0
Kinsley 1 tuần 2021-12-07T02:21:33+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-12-07T02:22:34+00:00

    Đáp án:

    $a,(x-1) ²+(x+3) ²=2(x-2)(x+1)+38$

    $=> x²-2x+1+x²+6x+9=(2x-4)(x+1)+38$

    $=> x²-2x+1+x²+6x+9=2x²+2x-4x-4+38$

    $=> x²+x²-2x²-2x+6x-2x+4x+1+9+4-38=0$

    $=> 6x-24=0$

    $=> 6x=24$

    $=> x=4$

    Vậy $S=${$4$}

    $b,5(x ²-2x-1)+2(3x-2)=5(x+1) ²$

    $=> 5x²-10x-5+6x-4=5(x²+2x+1)$

    $=> 5x²-10x-5+6x-4=5x²+10x+5$

    $=> 5x²-5x²-10x+6x-10x-5-4-5=0$

    $=> -14x – 14 =0$

    $=> -14x = 14$

    $=> x=-1$

    Vậy $S=${$-1$}

    BẠN THAM KHẢO NHA!!!

     

    0
    2021-12-07T02:22:56+00:00

    $a, (x-1)^2 + (x+3)^2 = 2(x-2)(x+1) + 38$

    $⇔ x^2 – 2x +1 + x^2 + 6x +9 = 2x^2 +2x -4x -4 +38$

    $⇔ x^2 -2x +x^2 +6x -2x^2 -2x +4x= -4 +38 -10$

    $⇔ 6x= 24$

    $⇔ x = 4$

    Vậy $S=\{4\}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )